What every engineer should know about patents - Konold, William G. (What every engineer should know, 1989)
"This useful, authoritative volume focuses on all aspects of intellectual property law with particular emphasis on patent laws enabling the reader to avoid such pitfalls as a loss of rights, and establish valid rights in inventions, trademarks, and writings. " - See more at: http://www.betterworldbooks.com/what-every-engineer-should-know-about-patents-id-0824780108.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.sF9POEMn.dpuf